2022
DOI: 10.3390/plants11030321
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining and Gene Expression Reveal Maytansine Biosynthetic Genes from Endophytic Communities Living inside Gymnosporia heterophylla (Eckl. and Zeyh.) Loes. and the Relationship with the Plant Biosynthetic Gene, Friedelin Synthase

Abstract: Even though maytansine was first discovered from Celastraceae plants, it was later proven to be an endophytic bacterial metabolite. However, a pure bacterial culture cannot synthesize maytansine. Therefore, an exclusive interaction between plant and endophytes is required for maytansine production. Unfortunately, our understanding of plant–endophyte interaction is minimal, and critical questions remain. For example: how do endophytes synthesize maytansine inside their plant host, and what is the impact of mayt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For instance, the application of an endophytic consortium improved crop production (Tripathi et al, 2020) and secondary metabolite production in different varieties of Catharanthus roseus (Singh et al, 2021b). The application of seven endophytic consortia enhanced maytansine biosynthesis, which is a potential antifungal agent (Pitakbut et al, 2022). Ganie et al (2022) recently examined the use of endophytes, especially their consortia, to obtain rice plants resilient to biotic and abiotic stress.…”
Section: Endophyte Application Strategymentioning
confidence: 99%
“…For instance, the application of an endophytic consortium improved crop production (Tripathi et al, 2020) and secondary metabolite production in different varieties of Catharanthus roseus (Singh et al, 2021b). The application of seven endophytic consortia enhanced maytansine biosynthesis, which is a potential antifungal agent (Pitakbut et al, 2022). Ganie et al (2022) recently examined the use of endophytes, especially their consortia, to obtain rice plants resilient to biotic and abiotic stress.…”
Section: Endophyte Application Strategymentioning
confidence: 99%
“…Howitz and Sinclair (2008) [42] hypothesized that homologous gene clusters present in plants and microorganisms may be cross activated by stress induced molecules, under certain conditions. A study by Pitakbut, Spiteller and Kayser (2022) [43] observed through gene analysis that endophytes associated with Gymnosporia heterophylla were responsible for the formation of maytansine through the expression of their AHBA synthase and halogenase genes. Alongside the expression of these genes and activation of the maytansine biosynthesis, the authors also observed an increase in the expression of the friedeline synthase genes in the plant.…”
Section: Integrating Multi-omics Approaches For Studying Endophytic R...mentioning
confidence: 99%
“…Moreover, two publications are concerned with the study of the effect of endophytes on plant secondary metabolism [ 9 , 10 ]. These studies described the influence of the grapevine bacterial and fungal endophytes on stilbene production in grape cells [ 9 ], the synthesis of cytotoxic macrolide maytansine by endophytes inside their plant host [ 10 ], and the impact of maytansine production on plant secondary metabolites [ 10 ].…”
mentioning
confidence: 99%